World Environmental and Water Resources Congress 2008 2008
DOI: 10.1061/40976(316)117
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Evapotranspiration-Based and Soil-Moisture-Based Irrigation Control in Turf

Abstract: A study was initiated in Fall 2006 in Raleigh, North Carolina to compare two types of commercially available irrigation control technologies, one based on estimates of evapotranspiration (ET) and the other based on feedback from soil moisture sensors. Water applied and turf quality from one ET-based system and two sensor-based systems were compared to a system using a standard time-based irrigation schedule. The effect of irrigation frequency was also a part of the study. Estimates of turf ET were obtained fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…Previous work has shown that water use efficiency can be improved through the addition of add-on sensors to existing irrigation controllers or through the use of more sophisticated controllers [3], [4], [8], [9], [10]. The types of control systems that are used in common practice can be classified as rainfall shutoff sensors (RS), soil moisture sensors (SMS) and evapotranspiration controllers (ET) [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work has shown that water use efficiency can be improved through the addition of add-on sensors to existing irrigation controllers or through the use of more sophisticated controllers [3], [4], [8], [9], [10]. The types of control systems that are used in common practice can be classified as rainfall shutoff sensors (RS), soil moisture sensors (SMS) and evapotranspiration controllers (ET) [9].…”
Section: Introductionmentioning
confidence: 99%
“…If used in an area with a large variance in terms of local climate, the performance of the unit may lead to less than optimal results. Extensive testing in North Carolina has shown that ET systems produced no savings in water due to overestimation in terms of evapotranspiration demands [8].…”
Section: Introductionmentioning
confidence: 99%
“…In their 2008 field study in Charlotte, N.C., Grabow et al found that smart controllers applied more water on average than standard operating systems or systems regulated by soil moisture. Turf quality was lower for both the standard timer and soil moisture-based systems, whereas systems with smart controllers provided the highest-quality turf with the best water efficiency (Grabow et al, 2008). Additional research is needed to confirm the type of smart systems in use and to determine the true efficiency of each type of irrigation system.…”
Section: Resultsmentioning
confidence: 99%
“…Time of operation (irrigation time -hrs per day) is calculated according to volume of water (water requirement -litres per day) required and the average flow rate of water (application rate -litres per hours). A timer starts and stops the irrigation process [8,9].…”
Section: Time Based Systemmentioning
confidence: 99%